Tetradecyl 2,3-Dihydroxybenzoate Improves the Symptoms of Diabetic Mice by Modulation of Insulin and Adiponectin Signaling Pathways - Xiang, Lan; Li, Jing; Wang, Yanhui; Tang, Ruiqi; Wang, Qian; Wu, Qiaobei; Qi, Jianhua (Frontiers in Pharmacology, 2017)
ABSTRACT: Background: Tetradecyl 2,3-dihydroxybenzoate (ABG-001) derived from Chinese medicine, gentiana regescens Franch is a leading compound with NGF mimic effect, it can induce neurite outgrowth of PC12 cells via the IGF-1/PI3K/ERK signaling pathway. Thus, we inferred that this compound had anti-diabetic effect and used streptozocin (STZ)-induced diabetic mice to indicate it. Methods: ABG-001 was synthesized with 2,3-dihydroxybenzoic acid and tetradecyl alcohol under certain reaction conditions. STZ-induced diabetic mice were used to investigate anti-diabetic effect. Oral glucose tolerance test (OGTT), insulin tolerance test (ITT), RT-PCR, Western blot, ELISA assays and histological section were performed to do the analysis of action mechanism. Results: ABG-001 showed anti-diabetic effect in STZ-induced diabetic mice. In diabetic mice, the anti-diabetic effect of ABG-001 at a dose of 20 mg/kg was equal with metformin at a dose of 140 mg/kg. Moreover, glucose tolerance and insulin sensitivity were significantly improved on diabetic mice. The plasma insulin, adiponectin and leptin were notably increased, whereas glucagon remarkably decreased. The gene expressions of adiponectin and leptin in adipose tissue, glucose transporter 4 and adiponectin receptor (ADR) 1 in liver and gastrocnemius, ADR2 in hypothalamus and pancreas were obviously increased. Conclusions: ABG-001 exerts antidiabetic effects via modulation of insulin and adiponectin signaling pathways. This new type of molecule could be a promising drug candidate for treatment of diabetes.